Crime and Punishment - Dostoyevsky, Fyodor; Translated with an afterword by Monas, Sidney (New York New American Library, 1981)
Determined to overreach his humanity and assert his untrammelled individual will, Raskolnikov, an impoverished student living in the St. Petersburg of the Tsars, commits an act of murder and theft and sets into motion a story which, for its excrutiating suspense, its atmospheric vividness, and its profundity of characterization and vision, is almost unequaled in the literatures of the world. The best known of Dostoevsky's masterpieces, Crime and Punishment can bear any amount of rereading without losing a drop of its power over our imagination.
Include Bibliography.
Keywords: Russia (Federation)--Saint Petersburg -- Murder -- Russia -- Psychological fiction